The Influence of Brand Experience on Brand Loyalty of South African smartphone users - Metedad, Rabia (University of the Witwatersrand, Johannesburg, 2024)
Less is known on the effect of brand experience on brand loyalty, more so within the context of South Africa's smartphone industry. What is evident, however, is the decrease in brand loyalty among South African consumers due to the overwhelming number of choices and technology available. Consumers who are very satisfied with their phones are less likely to transform this satisfaction into loyalty. The complexity of the relationship between consumers and brands has resulted in a decline in customer experience and brand commitment. The purpose of this study was to investigate the impact of brand experience on brand loyalty among South African smartphone users. This study was conducted using convenience and snowball sampling techniques. Data was collected from 398 respondents through a structured online questionnaire. The study focused on two popular smartphone brands, referred to as Brand A and Brand B for purposes of this study. Data was analysed using factor analysis and structural equation modelling using AMOS 28 software, measuring the relationship between brand experience dimensions (sensory, affective, behavioural, and intellectual) and brand loyalty dimensions (attitudinal and behavioural loyalty). The results showed that affective experience and intellectual experience are significant predictors of brand loyalty among SA smartphone users. In contrast, sensory experience and behavioural experience did not show a significant relationship with brand loyalty. Notably, Brand A smartphone users were found to be more loyal to their brand than Brand B smartphone users, evident in their ratings of affective and intellectual experiences, which were significantly higher than Brand B users.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in Strategic Marketing to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: brand experience; Sensory experience; Intellectual experience; Behavioural experience; Affective experience; Brand loyalty; Experiential marketing; Attitudinal loyalty; Behavioural loyalty; UCTD; SDG-8: Decent work and economic growth